Educational Values In The Waqf Of The Prophet's Companions and Its Implications For Indonesian Muslim Society (A Review Of The Waqf Hadiths Of Umar Bin Khattab, Utsman Bin Affan, and Abu Thalhah Al-Anshari) - Trisno Wardy Putra; Zulfahmi Alwi; Abdul Rahman Sakka (LP2M IAIN Palopo, 2024)
This research aims to add to the scientific treasure by emulating the waqf of the Prophet's companions and its implications for Muslim society in Indonesia. This method uses a qualitative approach with literature study as the main source of research. This research is specific in studying hadiths related to the waqf of Umar bin Khattab, Ustman bin Affan and Abu Talhah Al-Anshari. The results of the study explain some educational values that can be taken in developing the concept of waqf-based education, including competing in goodness, ta'awun in helping others, wealth as a means of charity jariyah, waqf with the best assets and the role of waqf that is growing and sustainable.